Functional and Radiological Outcome Analysis of Osteoperiosteal Decortication Flap in Nonunion of Tibia. (21st July 2021) - Kumar, Vineet; Waliullah, Shah; Avasthi, Sachin; Mahapatra, Swagat; Singh, Ajai; Ali, Sabir
Abstract : Introduction . The treatment of long bone shaft nonunions is challenging. The technique of osteoperiosteal decortications flap for approaching the nonunion site coupled with fixation modalities was first described by Judet in 1963. Despite promising clinical and radiological union, this technique is not popular among orthopaedic surgeons. Our study aimed to evaluate the radiological union and functional results of shaft tibia nonunions treated by the osteoperiosteal decortication approach. Methods . This retrospective study included all the cases with established tibial shaft nonunion following stringent inclusion and exclusion criteria and operated upon by following the principle of osteoperiosteal flap technique from April 2015 to July 2019. Further subgroups were made based on nonunions complexity based on nonunion scoring system (NUSS) score. The outcome measures included radiological union scale in tibial fractures (RUST) and lower extremity functional scale (LEFS). The preoperative scores for union and function were recorded, and the subsequent scores were obtained at three, six, and nine months and one year. Appropriate statistical analysis of the data was done. Results . Thirty-four cases were shortlisted for analysis, fulfilling our inclusion and exclusion criteria. There were 22 males (64.7%) and 12 females (35.3%) with a mean age of 34.17 ± 10.3 years. Subgroup analysis based on the complexity of nonunion (NUSS score) revealed 14 cases in group A, 10 cases in group B, 10 cases in group C, and 0 cases in group D. The average time from fracture to surgery in these cases was 14.6 months. The average time to achieve union was 9.6 months, with patients in groups A, B, and C, having a mean duration of 9, 10.5, and 12 months, respectively. Statistically, significant improvement was seen in both RUST scores and LEFS score. Complications included infection in seven cases, wound dehiscence in two cases, and four cases of persistent nonunion. Conclusion . Osteoperiosteal decortication remains a highly effective surgical technique in the management of nonunion of long bones. NUSS scoring is an essential tool for prognosticating nonunion cases. This score is inversely related to the radiological union (RUST score) of the bone and functional recovery (LEFS score) of the patient.